MODIFIKASI BERAS SINGKONG (RASI) MELALUI FERMENTASI BAKTERI ASAM LAKTAT (Modification of Rice-Cassava (Rasi) Through Lactic Acid Bacteria Fermentation) - Meutia, Yuliasri Ramadhani; Pohan, Hitler Guring; Aviana, Tita (Jurnal Hasil Penelitian Industri, 2013)
The aim of this research is to obtain better sensoric characteristic of ricecassava(rasi) as an alternative non rice food which has been consumed as staple food bythe people of Cireundeu village, West Java. With the increasing of sensory quality of rasihopefully can expand the puclic acceptance of this product. There are three designs usedin this study, first is the cassava fermented by lactic acid bacteria, second is the cassavaboth fermented by lactic acid bacteria and steamed, and third is the cassava bothfermented by lactic acid bacteria and dyed in boiling water. The highest yield is 23,69% onrasi which modified by fermentation of lactic acid bacteria without steaming or boiling.The organoleptic test showed that fermentation of cassava with lactic acid bacteria canincrease the hedonic value in terms of color, aroma, texture, and flavor it has a whitecolor, better aroma, texture, and flavor as compared to rasi without modification.